Effects of sulphide ion on corrosion behaviour of X52 steel in simulated solution containing metabolic products species: a study pertaining to microbiologically influenced corrosion (MIC). (May 2013) - Fatah, M C; Ismail, M C; Wahjoedi, B A
Abstract : The objective of this work is to study the effect of sulphide ion on the corrosion behaviour of X52 steel in the simulated solution containing sulphate reducing bacteria metabolic products species. Linear polarisation resistance and electrochemical impedance spectroscopy results show that the addition of 50 ppm sulphide ions increased the rate of X52 steel corrosion. However, with addition of 200 and 400 ppm sulphide, the corrosion rate decreased. The increase in corrosion rate is due to the increase in the cathodic reaction in the presence of sulphide, while the corrosion protection was related to FeS film formed, typically mackinawite and pyrite.